The design of an auricular acupoint probe with adjustable probe angle (一种可调节探头角度的耳穴探棒的设计) - ZHOU Yihan (周艺涵); XIE Wei (谢薇); REN Xiuya (任秀亚); DONG Huaqian (董画千); YUAN Dan (袁丹); XIANG Yiming (向毅明); ZHAO Lingling (赵玲玲); LUO Liyuan (罗丽媛) (中西医结合护理)
To design an auricular acupoint probe with adjustable probe angle, in order to detect the positive points of special parts of auricle more accurately. The probe rod is composed of a hand-held handle, a connecting rod and a probe. The characteristics of the probe are as follows: a primary angle adjusting device is provided at the connection of the hand-held handle and the connecting rod, and a secondary angle adjusting device is provided at the connecting end of the connecting rod and the probe. The probe is convenient for the operator to fix the hole in the special part of the earlobe, and is more beneficial to the operator to save force. The probe is easy to operate and suitable for all kinds of patients. It has good clinical application prospect and is worth popularizing. (设计一种可调节探头角度的耳穴探棒, 便于更准确探测耳郭特殊部位阳性点。该探棒由手持柄、连接杆、探头组成, 其特征在于: 在手持柄与连接杆的连接处设有第一角度调节装置, 在连接杆与探头的连接端设有第二角度调节装置。该探棒便于操作者对耳郭特殊部位定穴, 更利于操作者节力。该探棒操作方便, 且适用于各种患者, 具有较好的临床运用前景, 值得使用推广。)